Mechanistic insights into the reductive dehydroxylation pathway for the biosynthesis of isoprenoids promoted by the IspH enzyme1. Issue 10 (14th October 2015) - Abdel-Azeim, Safwat; Jedidi, Abdesslem; Eppinger, Jorg; Cavallo, Luigi
<x xml:space="preserve">Abstract</x> We report an integrated QM/MM study of the bio-organometallic reaction pathway of the reductive dehydroxylation of (E)-4-hydroxy-3-methylbut-2-enyl pyrophosphate (HMBPP).